2012
DOI: 10.1164/rccm.201112-2240oc
|View full text |Cite
|
Sign up to set email alerts
|

Viral Infection in Patients with Severe Pneumonia Requiring Intensive Care Unit Admission

Abstract: Viruses are frequently found in the airway of patients with pneumonia requiring ICU admission and may cause severe forms of pneumonia. Patients with viral infection and bacterial infection had comparable mortality rates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

32
292
10
18

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 305 publications
(368 citation statements)
references
References 37 publications
32
292
10
18
Order By: Relevance
“…A total of 27 articles encompassing 3215 patients met all the inclusion criteria and were included in the final analysis 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54. Of those 27, only eight studies, with 334 patients, provided the numbers or percentages of each bacterial coinfecting pathogen 28, 32, 33, 34, 38, 43, 46, 47. Thus, these eight studies formed the basis for identifying the most common coinfecting bacterial pathogens (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 27 articles encompassing 3215 patients met all the inclusion criteria and were included in the final analysis 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54. Of those 27, only eight studies, with 334 patients, provided the numbers or percentages of each bacterial coinfecting pathogen 28, 32, 33, 34, 38, 43, 46, 47. Thus, these eight studies formed the basis for identifying the most common coinfecting bacterial pathogens (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
“…All 27 included studies were observational, of which 13 (1218 patients) were prospective studies,30, 32, 33, 36, 40, 41, 43, 44, 48, 49, 50, 51, 52 and 14 (1997 patients) were retrospective analyses (Table 1). The majority (21) of studies were cohort studies, and the rest were case–control studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six studies reported that bronchoalveolar lavage was one of the diagnostic tools used to obtain a microbiological diagnosis [2,7,18,25,28,35]. However, only four of them reported the number of patients who had lower respiratory tract sampling [2,18,25,28].…”
Section: Resultsmentioning
confidence: 99%
“…The advent of PCR has greatly improved the identification of viruses in patients with CAP [1]. Over the last decade, several studies have used PCR to establish the importance of viruses in the aetiology of CAP [1][2][3][4][5][6][7][8][9][10][11][12]. An updated and objective literature review that quantitatively summarises and critically appraises the results of these studies is warranted.…”
Section: Introductionmentioning
confidence: 99%